The Analysis of Current Strength and Electrolysis Process Time of Silver (Ag) Plating on Copper Metal - Sarah Sihotang; Anggita Leontin Sitorus; Asep Wahyu Nugraha (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of adding time and increasing electric current strength to the electrolysis process on the quality of Ag metal coating on Cu metal. In this study, the electrolysis process was given different current variations, namely 4A, 6A and 8A and the electrolysis process time was 30, 45 and 60 minutes and the electrolyte concentration remained 0.6 M. To analyze the coating mass and thickness measurements were carried out while to determine the good quality of the coating process was determined using SEM. The results of the study showed that the best coating quality was 60 minutes of coating time and 8A current with a thickness of 4.85 μm. The SEM results to determine the good quality of the coating process on the surface of Ag metal on Cu metal can be seen in the copper sample (concentration 0.6 M, 60 minutes, 8A) which shows that the surface results on copper are slightly better and neater but there are still lots of copper sides which is not silver plated.